Regulation of angular impulse during two forward translating tasks - Mathiyakom, W.; McNitt-Gray, J. L.; Wilcox, R. R. (Journal of Applied Biomechanics, 2007)
Angular impulse generation is dependent on the position of the total body center of mass (CoM) relative to the ground reaction force (GRF) vector during contact with the environment. The purpose of this study was to determine how backward angular impulse was regulated during two forward translating tasks. Control of the relative angle between the CoM and the GRF was hypothesized to be mediated by altering trunk-leg coordination. Eight highly skilled athletes performed a series of standing reverse somersaults and reverse timers. Sagittal plane kinematics, GRF, and electromyograms of lower extremity muscles were acquired during the take-off phase of both tasks. The magnitude of the backward angular impulse generated during the push interval of both tasks was mediated by redirecting the GRF relative to the CoM. During the reverse timer, backward angular impulse generated during the early part of the take-off phase was negated by limiting backward trunk rotation and redirecting the GRF during the push interval. Biarticular muscles crossing the knee and hip coordinated the control of GRF direction and CoM trajectory via modulation of trunk-leg coordination.